Evaluation of a new semi-automated Hydragel 11 von Willebrand Factor multimers assay kit for routine use : Evaluation of a new von Willebrand Factor multimers assay kit - Pikta, Marika; Szanto, Timea; Viigimaa, Margus; Lejniece, Sandra; Balode, Dārta; Saks, Kadri; Banys, Valdas (Journal of Medical Biochemistry, 2020)
Accurate diagnosis and classification of von Willebrand disease are essential for optimal management.  The von Willebrand factor multimers analysis is in the phenotypic classification, especially in discrepant cases, an integral part of the diagnostic process. The aim of this study was to evaluate the performance of a new Hydragel 11VWF multimer assay (H11VW). Results: Comparison study did not reveal any significant difference between H5VW and H11VW.  The assessment of within-subject results, using H5VW and H11VW, demonstrates the reproducibility of the method in both healthy and VWD patients’ samples collected over time, with identical multimeric pattern on densitometric curves.Conclusion: This assay demonstrated acceptable performance, produced within-day results and can be used in routine practice for the visual investigation of gel and quantitative estimation of VWF multimer fractions.
Keywords: Electrophoresis, multimers, von Willebrand factor, von Willebrand disease